Will there be a season? The impact of COVID-19 on anxiety within NCAA student athletes compared to non-athlete university students - Peterman, K. (Digital Repository at the University of Maryland, 2021)
COVID-19 triggered psychological stress. College aged students and student athletes are among those vulnerable to mental health. The purpose of this study was to compare anxiety and potential moderators between student athletes and non-athlete students during the pandemic. Data were retrieved using survey methodology via Qualtrics. Student/athlete status was not related to anxiety (p=0.503). CF (p=<0.001), FFC (p=<0.001), and TFC (p=0.016) were associated with anxiety. There were no differences in coping between groups, however, greater TFC was related to greater anxiety in non-athlete students (p=< 0.001). Communication from AD`s (p=0.010) and teammates (p=0.033), as well as access to resources (p=0.036) were associated with anxiety in student athletes. Communication from coaches did not impact anxiety (p=0.545). Overall, anxiety during the pandemic was high. FFC may act as a protective factor, whereas TFC may worsen anxiety. Social support, access, and communication are crucial in times of uncertainty.